Death Anxiety in Muslim Iranians: A Comparison Between Youths, Middle Adults, and Late Adults. (April 2021) - Dadfar, Mahboubeh; Lester, David; Abdel-Khalek, Ahmed M.; Ron, Pnina
The study aimed to examine the levels of death anxiety between three age groups and compare gender-related differences among Iranian population. A total of 453 participants (252 college students, 55 middle-aged, and 146 old-aged) answered the Arabic Scale of Death Anxiety (ASDA). Significant differences were found between youths and old-aged samples and between middle-aged and old-aged samples on the ASDA scale. Old-aged persons showed more death anxiety than youths and middle-aged persons. There were also significant differences between men and women in total scores of the ASDA scale; men had more death anxiety than women. There were significant associations between age, gender, and death anxiety total scores. Limitations of the study include the use of a self-report scale, selection of a nongeneral nonclinical population, a Muslim religion, and an Iranian culture. Present results can be considered for psychological therapies for reducing death anxiety and pathways to death acceptance in Iranian people and for carrying out cross-cultural studies in other Asian, Arabic, Eastern, and Western countries with shared and nonshared religions and cultures in future studies.